2004
DOI: 10.1590/s1806-83242004000300003
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride does not induce DNA breakage in Chinese hamster ovary cells in vitro

Abstract: Fluoride has been widely used in dentistry because it is a specific and effective caries prophylactic agent. However, excess fluoride may represent a hazard to human health, especially by causing injury to genetic material. Genotoxicity tests represent an important part of cancer research to assess the risk of potential carcinogens. In the current study, the potential DNA damage associated with exposure to fluoride was assessed by the single cell gel (comet) assay in vitro. Chinese hamster ovary cells were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…(17,21). In addition, other authors showed that fluoride does not induce DNA damage (22). In this study it is proposed that F at 10 -3 M might trigger apoptosis by activating caspases signaling pathways.…”
Section: Discussionmentioning
confidence: 73%
“…(17,21). In addition, other authors showed that fluoride does not induce DNA damage (22). In this study it is proposed that F at 10 -3 M might trigger apoptosis by activating caspases signaling pathways.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore it is used for osteoporosis treatment (Astern et al 1998). Furthermore, fluoride has been widely used in dentistry as caries prophylactic agents (Ribeiro et al 2004). NaF was the first and still most recommended fluoride compound for fluoridation of drinking water (Ribeiro et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Animal systems may more accurately reflect human metabolism; however, they are expensive and time-consuming (requiring up to 3 years to complete); they are, therefore, not used as a first screen for genotoxicity or carcinogenicity. Thanks to the work of previous investigators, the single-cell, gel (comet) assay has been accepted as a rapid, simple, and reliable method of evaluating the genotoxicity of materials [15][16][17][18][19][20] . The basic principle of this assay is the migration of DNA fragments in an agarose matrix under electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…When viewed under a microscope, cells have the appearance of a comet, with a head (the nuclear region) and a tail containing DNA fragments or strands migrating toward the anode 20) . The studies of Ribeiro and coworkers have demonstrated that the single-cell gel (comet) assay is one of the suitable tools to investigate the genotoxicity of compounds used in dental practice [17][18][19] . Previous studies have demonstrated that MTA, whether gray or white, cannot induce geno-or cytotoxicity in mouse lymphoma or Chinese hamster ovary (CHO) cells, even after exposure to human peripheral lymphocytes ex vivo 20,21) .…”
Section: Introductionmentioning
confidence: 99%